Do Financially Constrained Firms Suffer from More Intense Competition by the Informal Sector? Firm-Level Evidence from the World Bank Enterprise Surveys - Julia Friesen; Konstantin Wacker (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2013)
This paper investigates which firms suffer from informal competition and highlights the role of access to finance in this context. We use cross-sectional data from the World Bank Enterprise Surveys covering 42,000 firms in 114 developing and transition countries for the period 2006 to 2011 and take discrete responses on the perceived severity of financial constraints and informal competition for our empirical analysis. We find that financially constrained firms face significantly more intense competition by the informal sector and that this effect is economically large. In fact, financial constraints are the most important reason why firms suffer from informal competition. Other influential variables are ill-designed labor market regulations, corruption, and firm size. A wide range of robustness checks substantiates this finding.
Keywords: C25; D21; O17; 330; Firm finance; informal competition; enterprise survey data; ordered logit model